Pulmonary gas exchange in heifersand milk productivity of firstborn cows of the simental breed of the Precarpathians of different constitution types - V. D. FЕDАK; М. І. PОLULIKH; О. І. SТАDNYTSKА; H. V. ILNYTSKA (Передгірне та гірське землеробство і тваринництво)
The results of research on pulmonary gas exchange in heifers and milk productivity of Simmental firstborn cows of Precarpathians of different types of constitution, which were evaluated according to the physiological and selection index developed by us, are presented. The control group included heifers and firstborn cows with a low physiological and selection index – a narrow-bodied type, and the experimental group, respectively – with a high physiological and selection index, wide-bodied type. In terms of depth of breathing, pulmonary ventilation, oxygen consumption, carbon dioxide excretion, total energy and heat production, individuals of the broad-bodied type in postnatal ontogeny significantly outnumbered their narrow-bodied counterparts.